Fabrication and photoelectrochemical characteristics of CuInS2 and PbS quantum dot co-sensitized TiO2 nanorod photoelectrodes1. Issue 64 (12th July 2015) - Han, Minmin; Jia, Junhong; Yu, Limin; Yi, Gewen
<x xml:space="preserve">Abstract</x> A cascade structured PbS/CuInS2/TiO2 photoelectrode with co-sensitization effect obtains the energy conversion efficiency of 4.11% under one sun illumination.